Cognitive disturbances at convalescents with the meningeal form tick-borne encephalitis and a mikst-infection - M. V. Nadezhdina; T. N. Fedchuk; M. G. Toporkova; N. I. Skulskaya; N. A. Mahnyova (Бюллетень сибирской медицины)
The operative, long-term memory (Mendelevich V.D. technique, 1999) and attention (proof assay of Burdon) at 96 convalescents with the meningeal form tick-borne encephalitis (CTBE) and 23 – mikst-infection (CMI) three age groups in late regenerative (6–12 months) and remote (till 2 years) the periods is investigated operative. The greatest is taped message comprehension quality indicators of a long-term memory and parameters of proof assay of Burdon. In the remote period сognitive disturbances were taped at all convalescents, prevailed at CMI and in III age group. Obtained data can form a basis for an expert estimation of state of health CTBE and CMI and prove medicamental correction at a stage of a dispensary observation.